Knowledge spillover effect in German Knowledge-Intensive Industries - Hájek, Petr; Stejskal, Jan (Universiti Utara Malaysia, 2016)
It is widely assumed that firms collaborating in R&D activities benefit from knowledge spillovers. This paper examines the role of three types of knowledge spillovers, namely internal, market and institutional. We demonstrate that German knowledge-intensive firms prefer internal knowledge transfer and market R&D collaboration, respectively. The empirical evidence shows that these tools promote innovation performance. We thus provide justification for this strategy. We also show that public financial support represents an effective measure for establishing R&D collaboration based on knowledge spillovers generated in the communication within the firm, in the market and with public institutions. The support of market and institutional R&D collaboration seems to be particularly important.
Znalostní přelévací efekty v německých znalostně intenzivních průmyslových odvětvích
Keywords: Knowledge; spillover; effect; German; Knowledge-Intensive; Industries; Znalostní; přelévací; efekty; německých; znalostně; intenzivních; průmyslových; odvětvích